LGBT Asylum claims: the case of South Africa - Hakizimana, Nancy (My University, 2018)
The idea of protecting human rights is a norm that is accepted and embraced in most modern nations. However, many of these nations still fail to meet certain human rights standards. Even in cases where human rights protections are explicitly stipulated in legislation, those legal protections are often inadequately operationalised. This dynamic is explored using the case of South Africa to investigate the propensity for the South African Department of Home Affairs to protect LGBT asylum seekers. A gap is identified between the South African legal landscape for asylum protection and the realisation of true protection for LGBT asylum seekers on a practical level. A document analysis clearly indicates the human rights obligations that South Africa has agreed to uphold - which equally encompasses the protection of LGBT asylum seekers. The specific challenges in adhering to these human rights obligations are contextualised through interviews with a lawyer that has dealt with several asylum cases as well as a representative from the Department of Home Affairs. This thesis concludes that although South Africa offers protection for LGBT asylum seekers in policy, there is still much work that needs to be done to ensure that true protection is realised in practice. Accordingly, this thesis provides recommendations of critical measures that the South African Department of Home Affairs could take to ensure better protection for LGBT asylum seekers.
Masters of Arts in International Relations Research Thesis, 2018